From strain to strength: a yearlong study on the transformative influence of inner engineering online program on mental well-being - Swaminathan, Ashwin; DeSchryver, Braiden; Rayapuraju, Akila; Barbaro, Julianna; Orui, Hibiki; Subramaniam, Balachundhar; Reed, Preeti Upadhyay (Frontiers in Psychology, 2025)
IntroductionHealth is a multidimensional phenomenon encompassing physical, mental, and social well-being, all of which are deeply interconnected. The COVID-19 pandemic highlighted the importance of mental and social health, as rates of loneliness, depression, and anxiety surged. Mindfulness practices, such as Shambhavi Mahamudra Kriya (SMK), have gained attention for their potential to enhance well-being by integrating breath regulation, meditation, and cognitive reframing techniques. During the COVID-19 pandemic, the Inner Engineering Completion Online (IECO) program was created to effectively teach SMK with global travel restrictions in effect. This study examines the long-term effects of SMK, taught through the IECO, on various measures of well-being over a one-year follow-up period.MethodsParticipants were recruited from the January 2020 IECO course. Participants completed surveys at consent, post-IECO, and 6 weeks, 6 months, and 1-year post-IECO. The surveys consisted of 4 validated neuropsychological scales: Perceived Stress Scale (PSS), Positive Emotion/Relationship/Engagement Scale (PERMA) Profiler, Pittsburgh Sleep Quality Index (PSQI), and Mindful Attention Awareness Scale (MAAS). Survey data was analyzed using linear mixed effect modeling. Two-sided p-values of <0.05 were considered statistically significant.ResultsHundred and eighty-eight participants were enrolled. Hundred and sixty-four participants completed baseline measurements, and 41 participants completed surveys at all timepoints. The baseline median [IQR] PSS score in participants was 13 [8, 18]; post-IECO median [IQR] PSS was 11 [8, 16] and 6-week median [IQR] PSS was 7 [4, 12], suggesting that consistent practice of Shambhavi Mahamudra Kriya resulted in reduced stress. This score was sustained up to a year post-IECO with a median [IQR] of 7 [3, 12]. The mean mindfulness scale (MAAS) score increased by 0.97 (95% C.I. 0.7–1.2 p < 0.01, η2p = 0.30) at the 1-year timepoint compared to baseline. The global PSQI score reduced at the week 6 timepoint by 1.3 (95% C.I. 0.49–2.0, p < 0.01) with medium effect size and was sustained until 1 year.DiscussionWithin 6 weeks of participating in IECO, regular practice of SMK significantly reduced stress, improved sleep quality, and boosted mindfulness. These benefits were sustained for at least a year with continued practice, suggesting that this practice is an effective path to maintaining general well-being.Clinical trial registrationClinicalTrials.gov, trial identification number NCT04189146.